PENDAMPINGAN PEMERIKSAAN KESEHATAN CALON JEMAAH HAJI KBIHU NURUL HARAMAIN KRAKSAAN PROBOLINGGO - Erin Nur Putriani; Moh. Affan; Misbahul Ulum; Samsul Hadi; Zainur Ridho (LPPM STAI Muhammadiyah Probolinggo, 2025)
A lack of understanding about the importance of maintaining health during the Hajj pilgrimage and low levels of compliance among pilgrims with health officials' recommendations are the main factors affecting the health of pilgrims in the field. In supporting the government's program aimed at ensuring pilgrims' readiness to participate in the series of Hajj activities, a common problem is the high incidence of illness among pilgrims during the pilgrimage. This situation is largely due to the lack of attention and supervision from Hajj organizers regarding health services, leading some pilgrims to neglect efforts to maintain their physical resilience. This service method employs a mentoring approach, with the aim of accompanying and assisting in the health examination process for Hajj pilgrims. The results of this service at KBIHU Nurul Haramain include the development of a health check schedule to ensure the smooth implementation of health checks. Additionally, several stages in the health examination process for pilgrims are outlined. The first stage is the medical examination (Medical Check-Up), which includes verifying the pilgrims' identities and reviewing their current health history, past medical history, and family medical history. After completing the first stage, the second stage involves a physical examination, including vital signs, body posture, inspection, and palpation of the skin, head, eyes, ears, and neck. This is followed by a chest examination, including the lungs and heart, muscle strength and reflex tests, and rectal and urogenital examinations. The final examination is a mental health assessment of the pilgrims.